Kontrol Sistem Mekanik Prototipe Robot Pengaduk Gabah Berbasis Internet of Things - Imran Habriansyah; Mukhtar Mukhtar; Peri Pitriadi; Remigius Tandioga; Firman Hamzah; Muh. Fahrun Rasyid; Yuhyil Jamalika (Politeknik Negeri Ujung Pandang, 2023)
Agriculture is an activity of managing biological natural resources carried out by humans to produce food, industrial raw materials or energy sources, as well as to manage their environment. Most farmers in Indonesia still use traditional/conventional methods in the grain drying process. However, for large-scale farmers this is certainly a difficult task for mixing grain. For this reason, a system is needed that can stir grain automatically so that farmers do not need to come directly to the drying area. In this study, a grain mixer robot was applied using energy from the sun, and can be controlled remotely. This robot uses solar panels to convert solar energy into electrical energy. This electrical energy is then stored in the battery. This energy will also be used to drive the robot to stir the grain. To move the robot, the user can adjust its direction and speed through an application on a smartphone. From this study, the best remote delay time is around 0.22 seconds, while the average delay time is around 0.8 seconds.